A review of the European Union countries on cross-border mergers and acquisitions market - Hoang Long Pham; Petr Marek (European Financial and Accounting Journal, 2019)
It is a well-known fact that the main objective of every corporation is to generate profits and enhance its shareholders' wealth. Corporate growth may be achieved either internally (through organic growth) or externally (through mergers and acquisitions). In parallel with global trends, corporate growth is achieved by cross-border mergers and acquisitions (M&As) that have increased dramatically in economies especially over the last few decades. It is also established that mergers and acquisitions come in waves - so far, six waves have been researched. The main aim of the presented paper is to analyse the activity of the European Union countries on the M&As market and to describe the main motives for cross-border M&As and how the performance of cross-merger M&As is measured.
Keywords: G39; 650; Cross-border Mergers and Acquisitions; Emerging Markets; Foreign Direct Investment; Performance Measurement